CVD graphene incorporating polymerized l-cysteine as an electrochemical sensing platform for simultaneous determination of dopamine and ascorbic acid. Issue 47 (23rd November 2017) - He, Danyu; Li, Shehong; Zhang, Pu; Luo, Hongxia
Abstract : A novel electrochemical sensor based on a poly-l -cysteine/graphene platform was developed for the simultaneous determination of dopamine and ascorbic acid. Abstract : A graphene platform electrode (GPE) was prepared directly by transferring chemical vapor deposited (CVD) graphene films from Cu foils to polyethylene terephthalate substrates with the aid of polymethyl-methacrylate, a distinct advantage over previously developed methods.l -Cysteine (l -Cys) was polymerized on the GPE by using a one-step electrodeposition technique to form a poly-l -Cys/GPE. As a negatively charged polymer, the poly-l -Cys could adsorb positively charged dopamine (DA) and repel negatively charged ascorbic acid (AA) under optimum conditions. As a result, a novel electrochemical sensor for the simultaneous determination of DA and AA was developed. The electrochemical behaviors of DA and AA were investigated by cyclic voltammetry. Differential pulse voltammetry was used for determining DA and AA in their mixture, where the separation between oxidation peak potentials of DA and AA was about 163 mV. The broad linear responses to DA and AA were determined by chronoamperometry, which were 0.2 to 423 μM and 1 to 580 μM with detection limits (S/N = 3) of 0.0531 μM and 0.2031 μM, respectively. In addition, the as-obtained sensor delivered good stability as well as high resistance to interference, and was successfully utilized in determining real samples. Consequently, the poly-l -Cys/GPE could be considered as a new promising DA and AA sensor, strongly indicating that CVD graphene could be used successfully as a material in electrochemistry.